Whistleblowing Intention, Personal Cost, Organizational Commitment, and Fraud Seriousness Level - Mirna Indriani; Aida Yulia; Nadirsyah Nadirsyah; Lisa Pira Ariska (Universitas Muhammadiyah Yogyakarta, Indonesia, 2019)
This study aims to investigate whether personal costs, seriousness level of fraud and organizational commitment play a role in influencing whistleblowing intentions. It is also intended to prove whether organizational commitment has a mediating effect on the relationship among personal costs, seriousness level, and whistleblowing intentions. The research subjects comprise of civil servants or contract employees of Government Institutions of Regencies/Cities in Aceh Province, Indonesia. The hypotheses were tested on 103 respondents who were selected using convenience sampling method. The data were collected using survey questionnaires sent via online using Google Form from May to July 2017. The data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of this study showed that personal costs and seriousness level of fraud influenced whistleblowing intentions. Nevertheless, it appeared that organizational commitment did not influence whistleblowing intentions. This study also proved that organizational commitment did not have a mediating effect on the relationship among personal costs and level of seriousness and whistleblowing intentions.